Vitamin D Deficiency and the Lung: Disease Initiator or Disease Modifier? - Foong, Rachel E. (MDPI, 2013)
Vitamin D deficiency is a global public health problem and has been associated with an increased incidence and severity of many diseases including diseases of the respiratory system. These associations have largely been demonstrated epidemiologically and have formed the basis of the justification for a large number of clinical supplementation trials with a view to improving disease outcomes. However, the trials that have been completed to date and the ongoing experimental studies that have attempted to demonstrate a mechanistic link between vitamin D deficiency and lung disease have been disappointing. This observation raises many questions regarding whether vitamin D deficiency is truly associated with disease pathogenesis, is only important in the exacerbation of disease or is simply an indirect biomarker of other disease mechanisms? In this review, we will briefly summarize our current understanding of the role of vitamin D in these processes with a focus on lung disease.